2009
DOI: 10.1098/rspb.2009.0517
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening and survival in free-living corvids

Abstract: Evidence accumulates that telomere shortening reflects lifestyle and predicts remaining lifespan, but little is known of telomere dynamics and their relation to survival under natural conditions. We present longitudinal telomere data in free-living jackdaws (Corvus monedula) and test hypotheses on telomere shortening and survival. Telomeres in erythrocytes were measured using pulsed-field gel electrophoresis. Telomere shortening rates within individuals were twice as high as the population level slope, demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
351
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(381 citation statements)
references
References 68 publications
20
351
7
Order By: Relevance
“…Indeed, early development is a period characterized by rapid telomere shortening [59], and faster telomere shortening early in life has been demonstrated in the wild, e.g. in jackdaws (Corvus monedula) [8]. Similarly, Andrew et al [61] showed that 49% of the variation in telomere length could be attributed to (environmental) family effects in a human twin study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, early development is a period characterized by rapid telomere shortening [59], and faster telomere shortening early in life has been demonstrated in the wild, e.g. in jackdaws (Corvus monedula) [8]. Similarly, Andrew et al [61] showed that 49% of the variation in telomere length could be attributed to (environmental) family effects in a human twin study.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length has been shown to significantly predict life-history parameters in a number of organisms, both when telomeres are measured early in life [4] and during adulthood [5]. For example, telomere length (or their rate of shortening) has been linked to lifespan in humans [6] and several bird species, both in captivity [4] and in natural populations [5,7,8]. More recently, it has been found that telomere length may not only be positively related to individual fitness through its link with lifespan, but also as a mediator of reproductive trade-offs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Class II telomere length [50] was analysed as described in Salomons et al [17], with some modifications. Briefly, we removed the glycerol buffer, washed the blood cells with 2 per cent EDTA and isolated DNA from erythrocytes (7 ml cells) using a CHEF Genomic DNA Plug kit (Bio-Rad, Hercules, CA, USA).…”
Section: (C) Telomere Length Analysismentioning
confidence: 99%
“…Telomere length dynamics have been correlated with rates of ageing and can predict future survival [11,12]. However, whether telomeres directly contribute to, or merely are affected by, the processes causing ageing is not known [13].…”
Section: Introductionmentioning
confidence: 99%